Vocational Education Program Implementation and Its Impact on Improving Graduate Quality - Anggun Dewi; Ralintang Pebuari Kustiko Aji; Muhamad Yasin Yusuf Al Asyuro; Muhammad Ulil Abror; Muhamad Mahfudh Mubarok (Journal of Educational Management Research, 2026)
This study aims to examine the implementation of the vocational program at SMK Al-Amnaniyah Karangjati. A descriptive qualitative research method was employed to obtain an in-depth understanding of the program’s implementation process. Data were collected through interviews, observations, and document analysis involving school leaders, teachers, and relevant stakeholders. The findings indicate that the vocational program is implemented as an effort to support government policies in improving students’ skills and work readiness. Although the program faces challenges, particularly related to inadequate facilities and infrastructure, its implementation can still be sustained by optimizing the available resources. The school continuously strives to improve program quality by strengthening collaboration and partnerships with various industry and workplace partners. The study implies that effective vocational program implementation requires not only adequate infrastructure but also strong institutional commitment and strategic partnerships. These findings can serve as a reference for vocational schools in developing adaptive strategies to enhance graduate quality despite resource limitations